Pengaruh Harga Emas Dunia, Harga Minyak Mentah Dunia dan Indeks Produksi Industri Terhadap Indeks Saham di Jakarta Islamic Index (JII) Dalam Jangka Panjang dan Jangka Pendek (Periode Januari 2005-Desember 2015) - Dwi Purnamasari; Raditya Sukmana (Jurnal Ekonomi Syariah Teori dan Terapan, 2017)
This research aims to know the influence of long-term and short-term world gold price, the price of crude oil to the world, and the index of industrial production against the stock index at the Jakarta Islamic Index (JII) during the period January to December 2015-2015. The object of this research is the stock index at the Jakarta Islamic Index (JII). Types of data used are secondary data. This research method using technical analysis with quantitative method of Error Correction Mechanism (ECM). The results showed that significant influence world gold prices in the long term and the short term against a stock index of JII. While the price of crude oil the world significant negative effect on the long run, and a significant positive effect on the short term. The index of industrial production turned out to be only a significant effect in the long term, but not in the short term.